Relationship of Systemic Inflammatory Markers and Body Mass Index with Primary Osteoarthritis: Inflammatory Markers and Body Mass Index in Osteoarthritis - Gulzar, Roma; Mahmud, Tafazzul E Haque; Rasheed, Aflak; Hafeez, Usman; Ahmed, Faizan (Pakistan Journal of Health Sciences, 2025)
Osteoarthritis (OA) is degenerative disorder which involves synovial inflammation. Erythrocyte sedimentation rate, Body mass index and C-reactive protein are commonly used markers to determine infection or inflammation. Objective: To measure the level of raised levels of erythrocyte sedimentation rate and C-reactive protein in primary osteoarthritis and to identify the association of body mass index with osteoarthritis in Pakistani population. Methods: This descriptive cross-sectional study was conducted at Department of Rheumatology, Shaikh Zayed Hospital, Lahore, Pakistan from July 2021 to April 2022. A total of 216 patients were enrolled. All patients over the age of 30 years with primary osteoarthritis were included. Association of C-reactive protein and erythrocyte sedimentation rate with OA grade and highest score in case of multiple joints were checked by using chi-square test and odds ratio. Results: Most were females and large group of individuals were overweight or obese. Mean BMI was 29.50 ± 4.94 kg/m2. The radiographic progression of OA was seen more in women compared to men for Grade 4 OA. The systemic inflammatory markers erythrocyte sedimentation rate and C-reactive protein were plotted against the Grade of OA and it was found that erythrocyte sedimentation rate was elevated in (n=118) most individuals however C-reactive protein was normal in the majority (n=196). Radiographic advancement of OA with the rise of these acute phase reactants was not significant i.e. p-value was 0.804 for erythrocyte sedimentation rate and 0.497 for C-reactive protein. Conclusion: There was no significant correlation between raised inflammatory markers and radiographic progression of osteoarthritis.